An investigation on devoutness Islamic prayer among female college students through biofeedback - Jing, Wang (2013)
Salah is the practice of formal prayer in Islam. Its supreme importance for Muslims is indicated by its status as one of the Five Pillars of Islam including positions of standing bowing prostrating and sitting. Salah is known to improve psychological, musculoskeletal and cerebral effects and gain significant health benefits healthy students. However, the psychophysiological analysis of devoutness-based Salah is scarce and often lack meticulous description to indicate positive effects of Salah. This study explored the experience of devoutness-based Salah training for female college students in Salah samples and compared them with respective controls. During the processes of performing Salah, The indexes of Heart Rate Variability (HRV), Electromyography (EMG), Skin Conductance Responses (SCR) and Phalange temperature (PT) were investigated. Four indexes were explored for the analysis of measured psychophysiological signals and for the analysis of procedures to performing Salah were explored. Psychophysiologically-driven instruments and data displays were built for analysis the devoutness-based Salah effects on improving autonomic nervous system response, assessing the health of muscles and mitigating stress, anxiety and depression symptoms. Furthermore, a group of subjects who practiced devoutness-based Salah for 22 days showed more pronounced improvement of the four indexes on day 22 compared to day 1. The control group did not show the evidence of a significant difference between day 1 and day 22. The results show that participation in performing devoutness-based Salah program can lead to significant reduction in levels of stress, anxiety and depression among female college students who had symptoms of stress, anxiety and depression. Furthermore, by evaluating the HRV, EMG, SCR and PT, this study demonstrates that the protocol is an opportunity to spend a little time in performing devoutness-based Salah, as well as achieves effectively autonomic nervous system balance, muscle relaxation, alleviation effects of normal daily stress and relaxation response occurs in association with the anxiety and depression. The results demonstrated that devoutness-based Salah may have clinical application in stress, anxiety and depression-related symptoms or it will alleviate the adverse effects of normal daily stress.